2022
DOI: 10.15789/1563-0625-aoi-2528
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-17A levels with immuneinflammatory profile and structural MRI data in patients with schizophrenia

Abstract: IL-17A is a proinflammatory cytokine involved in pathogenesis of some neuroinflammatory diseases of the brain. However, its role in schizophrenia is poorly understood. Currently, noninvasive neuroimaging techniques are widely used to assess abnormalities in brain morphology and interactions of neuronal networks in schizophrenia. The aim of this work was to study associations between IL-17A level and brain morphometric parameters in schizophrenia, in order to clarify immune factors of pathogenesis and search fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…According to our previous studies, elevated IL-17A levels are associated with marked immune abnormalities and with cortical morphometric changes in schizophrenia [4]. In this study, the G allele of SNP IL17A G-197A was shown to be associated with activation of systemic inflammation and signs of Th1 activation of the adaptive immune system in patients.…”
Section: Resultssupporting
confidence: 59%
“…According to our previous studies, elevated IL-17A levels are associated with marked immune abnormalities and with cortical morphometric changes in schizophrenia [4]. In this study, the G allele of SNP IL17A G-197A was shown to be associated with activation of systemic inflammation and signs of Th1 activation of the adaptive immune system in patients.…”
Section: Resultssupporting
confidence: 59%